Strategi Pembelajaran Berdiferensiasi Dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran PPKn Di SMP Negeri 21 Samarinda - Chatrisa Kinanthi; Jawatir Pardosi; Endang Herliah; Warman Warman; Asnar Asnar; Wingkolatin Wingkolatin (Lembaga Pengembangan Kinerja Dosen, 2024)
The research aims to describe the strategies effectively employed by Civics teachers in enhancing students' understanding of Civics subjects and the impact of differentiated learning. It is a descriptive qualitative study. Data analysis was conducted through observation, interviews, and documentation, followed by data analysis stages of data reduction, data presentation, and conclusion drawing. The results indicate that differentiated learning strategies begin with diagnostic assessment to identify students' needs regarding readiness, interests, and learning styles, enabling teachers to develop more targeted and responsive teaching strategies. The differentiated learning strategies utilized include differentiation of content, process, and product. The positive impact of differentiated learning includes students feeling accepted without distinction from smarter peers, engaging in collaborative learning processes, confidently participating in class discussions, and expressing topics discussed during lessons